2021
DOI: 10.2196/31774
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Information Sources and Health Behaviors During Pregnancy: Results From a Prenatal App-Embedded Survey

Abstract: Background Pregnancy is a time of heightened COVID-19 risk. Pregnant individuals’ choice of specific protective health behaviors during pregnancy may be affected by information sources. Objective This study examined the association between COVID-19 information sources and engagement in protective health behaviors among a pregnant population in a large academic medical system. Methods Pregnant patients comple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Pregnancy is an intense information-seeking phase [ 52 ]. Information trusted by pregnant women influences health decisions, behavior, and vaccine acceptance [ 53 ]. Information sufficiency is also shown to positively influence pregnancy satisfaction [ 54 ].…”
Section: The 5-p Vaccine Acceptance Model In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is an intense information-seeking phase [ 52 ]. Information trusted by pregnant women influences health decisions, behavior, and vaccine acceptance [ 53 ]. Information sufficiency is also shown to positively influence pregnancy satisfaction [ 54 ].…”
Section: The 5-p Vaccine Acceptance Model In Pregnancymentioning
confidence: 99%
“…It has also been shown that for many women, vaccine decision-making for the infant commences during their pregnancy [ 52 ]. Given the heightened risk to pregnant women that COVID-19 presents, numerous studies have shown that pregnant women are highly engaged in information-seeking behavior related to COVID-19 infection and vaccines [ 53 ]. Conversely, in a study of COVID-19 vaccine uptake during pregnancy, the most cited reason for hesitancy was a lack of knowledge about the vaccine [ 31 ].…”
Section: The 5-p Vaccine Acceptance Model In Pregnancymentioning
confidence: 99%
“…21 Fitur yang tersedia termasuk konten pendidikan menurut minggu kehamilan, karakteristik demografis dan klinis pengguna, jumlah gerakan janin dan pengatur waktu kontraksi, peluang untuk mendokumentasikan pengalaman kehamilan, dan pemeriksaan rutin untuk gejala serta risiko psikososial.21 Aplikasi ini juga menawarkan sumber daya yang relevan (misalnya layanan kesehatan setempat) atau tindakan (misalnya menghubungi penyedia layanan), tanda atau gejala Covid-19 (alat skrining Covid-19), pelaporan gejala dengan panduan pencarian pengobatan serta kuesioner perilaku Covid-19. 22 Konten medis di aplikasi My Healthy Pregnancy bersumber dari organisasi dan pedoman ahli seperti American College of Obstetricians and Gynecologists (ACOG), Pusat Pengendalian dan Pencegahan Penyakit (CDC) dan publikasi jurnal peer-review. Draf akhir konten akan ditinjau oleh para profesional medis, termasuk spesialis kedokteran ibu dan janin.21 Perlu adanya panduan khusus tentang aplikasi terkait sumber informasi dari ACOG, CDC dan publikasi jurnal.…”
Section: Negara Maju Amerika Serikatunclassified
“…There are women who carefully follow treatment plans and receive the required medical treatment as is; on the other hand, there are women who choose not to accept the recommendations accurately and change them accordingly when they feel they are not beneficial for them [40][41][42]. Specifically, it is known that socio-demographic factors and socio-cultural contexts may influence decision-making regarding the PHBs of pregnant women against the Coronavirus [27,43]. Therefore, it is important to examine the contribution of such background factors in predicting PHB against the Coronavirus among pregnant women.…”
Section: Health Behaviors Among Pregnant Womenmentioning
confidence: 99%